The Validation of Learning Management System in Mechanics Instruction for Prospective Physics Teachers - Ni Made Yeni Suranti; Gunawan Gunawan; Ahmad Harjono; Agus Ramdani (Department of Physics Education, Universitas Mataram, 2020)
Improving the quality of education is done by improving the quality of learning devices. Learning devices are important to facilitate students' conceptual understanding and creativity. Utilization of information technology such as the use of learning management systems (LMS) can make learning effective. The final goal of this research is to produce LMS tools in mechanics courses that are feasible to use and can improve students' conceptual understanding and creativity. This study is a research and development using a 4-D model consisting of 4 stages of define, design, develop, and disseminate. The validity test was conducted by 3 expert lecturers and it was concluded that the device developed was suitable for use. Expert assessment on learning devices is reliable, which means there are no significant differences in each assessment. Criticisms and suggestions given are used as material for revision/improvement so that learning devices are obtained that are intact and ready to be used for learning.